(3JShjb GdNOeGJ GdeUQajI (B:s (3eONd fXQj JWHjbj (B/s - (3GMeO, eMehO GMeOs ((3YeGf(B: s (3OGQ GdHQcI ddfTQ hGdJhRjY(B, s, 2001)
(3Gf GdcJGH ceG gh ehVM aj eMJhjGJg jJVef LGfHjf CSGSjjf ef GdLGfH GdYdej hGdLGfH GdJWHjb HMK jCJj eJcGedG hTGedG ef MjK GdWQhMGJ hOQGSI GdMGdI hGdJMdjdGJ hGdGSJQGJjLjGJ hGdSjGSI GdNGUI HJShjb GdNOeGJ GdeUQajI aj YGde CUHMJ ajg GdUfGYI GdeUQajI JYjT MGdI efGaSI TOjOI (B.s
Keywords: (3GdHfhcs; (3GdJShjbs; (3NOeGJ eUQajIs